2018
DOI: 10.4269/ajtmh.17-1014
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Immunogenicity, and Protective Efficacy against Controlled Human Malaria Infection of Plasmodium falciparum Sporozoite Vaccine in Tanzanian Adults

Abstract: Abstract.We are using controlled human malaria infection (CHMI) by direct venous inoculation (DVI) of cryopreserved, infectious Plasmodium falciparum (Pf) sporozoites (SPZ) (PfSPZ Challenge) to try to reduce time and costs of developing PfSPZ Vaccine to prevent malaria in Africa. Immunization with five doses at 0, 4, 8, 12, and 20 weeks of 2.7 × 105 PfSPZ of PfSPZ Vaccine gave 65% vaccine efficacy (VE) at 24 weeks against mosquito bite CHMI in U.S. adults and 52% (time to event) or 29% (proportional) VE over 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
186
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(197 citation statements)
references
References 35 publications
(61 reference statements)
5
186
1
Order By: Relevance
“…Strikingly, the comparison of PfSPZ vaccine-induced antibody titers specific for the P. falciparum circumsporozoite protein (PfCSP) showed significantly lower titers in malaria preexposed than malaria-naive individuals immunized with the PfSPZ Vaccine using comparable regimen [8]- [11]. These differences in PfSPZ vaccine-induced immunity was also observed between vaccinees residing in malaria endemic countries including Tanzania, Mali and Equatorial Guinea [11]- [13].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Strikingly, the comparison of PfSPZ vaccine-induced antibody titers specific for the P. falciparum circumsporozoite protein (PfCSP) showed significantly lower titers in malaria preexposed than malaria-naive individuals immunized with the PfSPZ Vaccine using comparable regimen [8]- [11]. These differences in PfSPZ vaccine-induced immunity was also observed between vaccinees residing in malaria endemic countries including Tanzania, Mali and Equatorial Guinea [11]- [13].…”
Section: Introductionmentioning
confidence: 93%
“…Serum samples for anti-PfCSP antibody evaluation were collected before vaccination (baseline) and days post last vaccination. Anti-PfCSP total IgG levels were measured by enzyme linked immunosorbent assay (ELISA) as described [11,31,32].…”
Section: Serological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The vaccine was well-tolerated in a clinical trial in Malí [24], having 29% efficacy against heterologous strains during 24-week (~ 6 month) follow-up without incurring in any serious local or systemic adverse events (AE). Effectiveness 3 to 24 weeks (~ 1 to 6 months) after the last immunization was evaluated by homologous intravenous CHMI which showed that 20% of the subjects who received 5 doses of 2.7 × 10 5 PfSPZ had become fully protected [25].…”
Section: Adultsmentioning
confidence: 99%
“…Higher Abs responses in children and infants who had been less exposed to P. falciparum [28] and subjects living in non-endemic areas [27] suggested that Africans' reduced immune responses were due to immunoregulation following long-term exposure to P. falciparum infection [24,25]. All such efforts have shown that PfSPZ efficacy in adults who have not had prior exposure to P. falciparum depends on the administration route (to induce tissue resident T cells in the liver) and the dose (which determines the degree of protection durability against homologous and heterologous challenge).…”
Section: Adultsmentioning
confidence: 99%